Editorial - Arts & Culture for All (Special Issue) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
We are living in a troubled and troubling world: globally, locally and, increasingly, personally. A world of violence, insecurity and fear. Palestinian author Isabella Hammad's concern that 'violence can make art-making seem futile and feeble, easily crushed' (2023) must resonate for many of those who work with people experiencing increasingly harsh living conditions.  Her conclusion, however, is instructive: 'It's easy to feel useless, and from there it's a short leap to despair. But I don't believe we can afford to despair, nor do I think despair is ethical'. This sense of a duty to resist despair is a striking reminder of the critical task of educators and activists, and of the role that arts and culture can play in sustaining energy, determination and defiance in the face of despair. In this special issue of Concept, authors draw attention to some of the ways that people collectively make sense of, re-imagine or seek to change, the conditions of their lives by using the arts as a means and space of engagement.